2016
DOI: 10.1111/ens.12168
|View full text |Cite
|
Sign up to set email alerts
|

Small sweat bees (Hymenoptera: Halictidae) as potential major pollinators of melon (Cucumis melo) in the Mediterranean

Abstract: In the current scenario of a general decline of the honeybee worldwide, studies on the potential of alternative bee species in pollinating cultivated plants are important. Although melon, Cucumis melo, is a crop with great commercial importance, there is very little information on its pollinating fauna in Europe, and none from the southern Mediterranean area. In a locality in central Spain, using both pan‐traps and net collections, we found that melon flowers are visited by 31 species of bees spanning four fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
4
12
0
Order By: Relevance
“…We have focused on this group because it was the most abundant in both the flower strip and the melon flowers, and because some small bees belonging to the family Halictidae (genus Lassioglossum spp.) have been previously identified as a key pollinators of the melon crop in Central Spain, such as the eusocial L. malachurum (Kirby, 1802) [52], which is also seen in our study. In 2013, the most visited plant for these bees was B. officinalis, which does not have a high pollen content and mainly supplies nectar [75]; therefore, this could have probably generated an increase in pollinator foraging activity, trying to seek pollen in nearby resources such as the melon crop.…”
Section: Visits To the Melon Crop And The Role Of The Flower Strip Assupporting
confidence: 83%
See 2 more Smart Citations
“…We have focused on this group because it was the most abundant in both the flower strip and the melon flowers, and because some small bees belonging to the family Halictidae (genus Lassioglossum spp.) have been previously identified as a key pollinators of the melon crop in Central Spain, such as the eusocial L. malachurum (Kirby, 1802) [52], which is also seen in our study. In 2013, the most visited plant for these bees was B. officinalis, which does not have a high pollen content and mainly supplies nectar [75]; therefore, this could have probably generated an increase in pollinator foraging activity, trying to seek pollen in nearby resources such as the melon crop.…”
Section: Visits To the Melon Crop And The Role Of The Flower Strip Assupporting
confidence: 83%
“…Those visitors captured in the melon flowers were noted down. Species present in Central Spain were identified according to the Atlas of Hymenoptera [60] and Ortiz-Sánchez [61], and some of them were already well-known [32,52,55].…”
Section: Visitor Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Melon is a plant pollinated by insects only. When the period of keeping melon plants under cover is extended, fruit yields may decline because pollinating insects have more difficulty gaining access to the flowers [26]. In the present study, the length of plant covering period did not affect yield levels, which is consistent with the findings by Santos et al [27] who reported that the length of melon plant covering period (18,21,24,27, and 30 days) did not significantly influence fruit yields.…”
Section: Discussionsupporting
confidence: 91%
“…Wild bees are also vital, and often better than Apis, as crop pollinators, with the importance of honeybees often over-emphasised in the past (see Breeze et al 2011;Garibaldi et al 2013). For example, halictid bees are important for melon (Rodrigo-Gomez et al 2016) and watermelon (Garantonakis et al 2016), bumblebees are important for blueberries (Button and Elle 2014) and several wild bees are better than managed honeybees at pollinating apples (Mallinger and Gratton 2015), although it is only a few relatively common solitary bee species that are crucial across crops in general (Kleijn et al 2015). Table 5 Heterospecific deposition by different groups of bees and non-bees for all plant species pooled, at each study site.…”
Section: Discussionmentioning
confidence: 99%